A Sociologist among the Spirits. (9th September 2019) - Singleton, Andrew
Abstract : This article is an academic autobiography of Andrew Singleton, an Australiansociologist of religion whose work focuses on applied, mixed-methodsstudies of youth religion, religious belief and new religious movements.It starts with a sociology of religion class, describes graduate researchthat utilised qualitative methods, and post-doctoral work in quantitativemethods, and then concludes by discussing recent mixed-methodsprojects. The career arc of an academic is shaped by the legacy of earlierscholars in the field, key mentors, opportunities for research support andcollaborators. The article emphasises the role and importance of these factorsin forming an individual's professional profile and the kind of scholarshipthey produce.